2004
DOI: 10.3171/ped.2004.100.2.0142
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in children with moyamoya syndrome after cranial revascularization by pial synangiosis

Abstract: Following pial synangiosis, the majority of pediatric patients with moyamoya syndrome stop having strokes and TIAs, and they appear to experience an excellent long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
451
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(482 citation statements)
references
References 26 publications
24
451
1
6
Order By: Relevance
“…[10,31] This report is congruent with previous observations that early postoperative neurological deficits usually resolve within 7 days, while irreversible cerebral infarction may persist in some patients with or without neurological deficits. [12] The incidence of transient neurological events varies among different reports, and it seems that studies from Asian countries showed a higher rate of postoperative stroke than those from America.…”
Section: Discussionsupporting
confidence: 81%
“…[10,31] This report is congruent with previous observations that early postoperative neurological deficits usually resolve within 7 days, while irreversible cerebral infarction may persist in some patients with or without neurological deficits. [12] The incidence of transient neurological events varies among different reports, and it seems that studies from Asian countries showed a higher rate of postoperative stroke than those from America.…”
Section: Discussionsupporting
confidence: 81%
“…4,6,[8][9][10]14) CBF studies have been performed in 11 moyamoya disease patients with chorea including the present case (Table 1). 2,[4][5][6][8][9][10]17,18) Even if MR imaging showed no damage of the basal ganglia, basal blood flow reduction or decreased vascular reserve in basal ganglia was noted in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the quasi-MMD is a rare disease. It is reported that the ratio of quasi-MMD is higher in western country [11]. Regarding with clinical manifestation of MMD, it is well known that the pediatric patients present with ischemic attack and adult patients tend to suffer from intracranial hemorrhage [12,13].…”
Section: Discussionmentioning
confidence: 99%